Classification of Educational Tasks From the Mother Language - ugli, Zokirov Javohir Gaybullo (Journal of Higher Education and Academic Advancement, 2024)
In the article, the priority of the development of practical speech skills in language education today, the inclusion of pragmatic competence in the composition of speech competences, starting from school education in students, the ability to speak in accordance with the speech situation, becoming a participant in dialogue, polylogues, being able to engage in polemics with interlocutors and justifying one's opinion it is thought about training competence.